Selenium dioxide-promoted selective synthesis of mono- and bis-sulfenylindoles. Issue 12 (16th May 2018) - Thurow, Samuel; Penteado, Filipe; Perin, Gelson; Alves, Diego; Santi, Claudio; Monti, Bonifacio; Schiesser, Carl H.; Barcellos, Thiago; Lenardão, Eder J.
Abstract : Easy access to mono- and bis-sulfenylindoles using the SeO2 /I2 system. Abstract : A selective method for the preparation of mono- and bis-sulfenylindoles was developed using an oxidizing agent and the I2 /SeO2 system as an efficient catalyst. The selectivity was controlled by varying the amount of SeO2 . This represents the first example of the application of SeO2 in this type of selective chemistry.